Lanthano phosphomolybdate-decorated silica nanoparticles: novel hybrid materials with photochromic properties1. Issue 10 (14th March 2015) - Pinto, Tânia V.; Fernandes, Diana M.; Pereira, Clara; Guedes, Alexandra; Blanco, Ginesa; Pintado, Jose M.; Pereira, Manuel F. R.; Freire, Cristina
<x xml:space="preserve">Abstract</x> Novel hybrid nanomaterials prepared through the immobilization of phosphomolybdates onto functional silica nanoparticles revealed promising photochromic properties under UV irradiation.